Motivasi Siswa dalam Mengikuti Ekstrakurikuler Sepak Bola pada Siswa SMP Negeri 1 Talang Kelapa Banyuasin - Abdu Rakhman; Ferri Hidayad; Puput Sekar Sari (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The problem in this research is how many factors influence students' motivation in taking part in extracurricular football activities at SMP Negeri 1 Talang Kelapa Banyuasin, including intrinsic and extrinsic factors. This research aims to identify how much factors influence student motivation in participating in extracurricular football activities at school, including intrinsic and extrinsic factors. This research is quantitative research using motivational methods and collecting information or data using questionnaires. Based on the results of the research carried out using the questionnaire method, the results showed that in general the motivation of students in participating in extracurricular football at SMP Negeri 1 Talang Kelapa Banyuasin was in the very high category. This is shown by the percentage value obtained from student motivation of 55% which is categorized as very high while 45% is categorized as high. Based on the results of the research and discussion above, extracurricular football at SMP Negeri 1 Talang Kelapa Banyuasin is in the very high category.